2015
DOI: 10.1007/s11060-015-1982-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of combined visualization of MR diffusion and perfusion maps in glioblastoma

Abstract: We analyzed whether the combined visualization of decreased apparent diffusion coefficient (ADC) values and increased cerebral blood volume (CBV) in perfusion imaging can identify prognosis-related growth patterns in patients with newly diagnosed glioblastoma. Sixty-five consecutive patients were examined with diffusion and dynamic susceptibility-weighted contrast-enhanced perfusion weighted MRI. ADC and CBV maps were co-registered on the T1-w image and a region of interest (ROI) was manually delineated encomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Several previous reports have focused on the usefulness of both PWI and DWI in unselected glioma patients to differentiate histopathologic grades and, more recently, for stratifying patients into prognostic groups 17,32,36,[38][39][40][41] . However, distinguishing different histopathologic grades and survival times in patients with diffuse glioma grade II and grade III, especially oligodendroglial tumors, is challenging with considerable overlap between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports have focused on the usefulness of both PWI and DWI in unselected glioma patients to differentiate histopathologic grades and, more recently, for stratifying patients into prognostic groups 17,32,36,[38][39][40][41] . However, distinguishing different histopathologic grades and survival times in patients with diffuse glioma grade II and grade III, especially oligodendroglial tumors, is challenging with considerable overlap between groups.…”
Section: Discussionmentioning
confidence: 99%
“…ADC maps and T1w images were coregistered using a linear rigid registration algorithm based on mutual information followed by visual inspection to ensure adequate alignment [27,28]. …”
Section: Methodsmentioning
confidence: 99%
“…GBMs with high relative CBV were significantly associated with a poor OS, while another study by Deike et al 45 in 2016 suggested that GBMs with a low blood supply may be associated with poor OS. The difference in results between these studies may be due to the different postoperative treatment strategies.…”
Section: In 2008 Found Thatmentioning
confidence: 96%